Primary Systemic Amyloidosis Presenting as Skin Vegetations: A Case Report - Meng-Hua Li; Li-Ming Wu (Wolters Kluwer Health, 2022)
Introduction:. Primary systemic amyloidosis is characterized by clonal plasma cell disorder, and its signs and symptoms are various and complex, damage to the skin and mucous membrane is often more likely to attract attention.Here we reported a case of a 61-year-old male patient who presented with topical mucocutaneous lesion, as well unusual skin vegetations. Case presentation:. A 61-year-old man was hospitalized due to repeated burning sensation on his back, multiple ecchymosis, and skin vegetations. Through a series of examinations (mainly including skin histopathology, bone marrow cytology, bone marrow flow cytometry, immunofixation electrophoresis), Primary systemic amyloidosis was diagnosed, but multiple myeloma could not be diagnosed. Subsequently, he received chemotherapy. In the half-year follow-up, there was no significant change in his symptoms and signs. Discussion:. In this case, in addition to the typical skin damage of primary amyloidosis, the multiple skin vegetations in the buttocks, abdomen, and arms are particularly noteworthy. According to the histopathology and Immunohistochemistry of the skin vegetation, we infer that the formation mechanism of these skin vegetation is lymphatic obstruction caused by amyloid, which leads to lymphatic dilatation, lymph leakage, and dermal edema. Conclusion:. Primary systemic amyloidosis is a rare disease, which is often difficult to diagnose. We should be alert to those atypical skin features so as not to delay diagnosis.